Pharmacological Treatment of Diabetic and Non-Diabetic Patients With Coronary Artery Disease in the Real World of General Practice - Rottura, Michelangelo; Molonia, Antonino; Giorgi, Domenico Antonio; Marino, Sebastiano; Scoglio, Riccardo; Pallio, Giovanni; Irrera, Natasha; Imbalzano, Egidio; Altavilla, Domenica; Squadrito, Giovanni; Squadrito, Francesco; Arcoraci, Vincenzo (Frontiers in Pharmacology, 2022)
Type 2 diabetes mellitus (T2DM) severely increases the probability of developing coronary artery disease (CAD), and diabetic patients with CAD should be considered at very high cardiovascular risk. The complexity of this clinical scenario makes very hard the appropriateness of the pharmacological treatment in the real world. To investigate the implementation of guideline recommendations for the treatment of patients affected by CAD with or without T2DM, a retrospective observational study was carried out between 2018 and 2020, by using the computerized clinical medical record of 10 general practitioners (GPs) including 13,206 subjects. A total of 926 patients (7.0%) were affected by CAD and 393 (42.4%) of them were also diabetic. LDLc, SBP, DBP, and FPG were recorded in 77.4%, 65.4%, 66.5%, and 82.6% of patients, respectively. Comorbidities (median; IQR = 8; 6–10 vs. 5; 3–7: p < 0.001) were significantly high in diabetic patients. Specialist counselling has been observed in 59.9% of diabetic and 57% of non-diabetic patients (p = 0.400). Antithrombotic drugs, statins, β-blockers, or RAASs were prescribed in 67.2%, 59.6%, and 75.9% of patients, respectively. Overall, 462 (49.9%) patients used the treatment suggested by guidelines. Dyslipidemia, hypertension, atherosclerosis, and specialist counselling were predictors of suggested drugs use both in diabetic and non-diabetic patients. Diabetes was not an independent factor related to the likelihood to be properly treated, according to the guidelines. Glucose lowering drugs were prescribed in 69.5% of diabetic patients, but only 39 (14.3%) were treated with the proper GLP-1 or SGLT2-i, whereas 45 patients (16.5%) received the improper sulphonylureas. Our results showed that a “non-ideal” therapeutic approach was adopted in patients affected by diabetes and CAD. ADA and ESC guidelines recommend the use of at least one hypoglycemic agent belonging to the GLP-1 or SGLT2-i class in diabetic patients with high/very high cardiovascular risk, regardless of the glycemic target (HbA1c <7%). However, only a few diabetic patients on hypoglycemic therapy were appropriately treated. These data suggest that a closer collaboration between the GPs, clinical pharmacologist, and specialists is needed in the real world scenario of the general practice in order to effectively improve adherence to guidelines and overall management of global cardiovascular risk in diabetic patients.